S100A4 as a target of the E3-ligase Asb2β and its effect on engineered heart tissue - Braumann, Simon Pascal; Doroudgar, Shirin (Frontiers in physiology, 2018)
Background: S100A4 has recently emerged as an important player in cardiac disease, affecting phenotype development in animal models of myocardial infarction and pathological cardiac hypertrophy, albeit it is unclear whether S100A4 exerts a detrimental or beneficial function. The goal of the current study was to analyze S100A4 expression in models of cardiac pathology, investigate its degradation by the ubiquitin-proteasome system and furthermore examine the functional effects of S100A4 levels in a 3D model of engineered heart tissue (EHT). Methods and Results: S100A4 mRNA and protein levels were analyzed in different models of cardiac pathology via quantitative RT-PCR and Western blot, showing a higher S100A4 steady-state protein concentration in hearts of Mybpc3-knock-in (KI) hypertrophic cardiomyopathy (HCM) mice. COS-7 cells co-transfected with plasmids encoding mutant (MUT) Asb2β lacking the E3 ligase activity in combination with V5-tagged S100A4 plasmid presented higher S100A4-V5 protein steady-state concentrations than cells co-transfected with the Asb2β wildtype (WT) plasmid. This effect was blunted by treatment with the specific proteasome inhibitor epoxomicin. Adeno-associated virus serotype 6-mediated S100A4 overexpression in a 3D model of EHT did not affect contractile parameters. Immunofluorescence analysis showed a cytosolic and partly nuclear expression pattern of S100A4. Gene expression analysis in EHTs overexpressing S100A4-V5 showed markedly lower steady-state concentrations of genes involved in cardiac fibrosis and pathological cardiac hypertrophy. Conclusion: We showed that S100A4 protein level is higher in cardiac tissue of Mybpc3-KI HCM mice probably as a result of a lower degradation by the E3 ligase Asb2β. While an overexpression of S100A4 did not alter contractile parameters in EHTs, downstream gene expression analysis points towards modulation of signaling cascades involved in fibrosis and hypertrophy.
Gesehen am 05.08.2019